Front- or rear-weighted track start or grab start: Which is the best for female swimmers? - Welcher, R. L.; Hinrichs, R. N.; George, T. R. (Sports Biomechanics, 2008)
The aim of this study was to compare three competitive swimming starts (grab, rear-weighted track, and front-weighted track). The starts were compared in terms of time and instantaneous horizontal velocity, both at take-off from the block and at 5 m from the wall. Twenty US college female swimmers performed three trials of each of the three randomly ordered starts. Swimmers left the block significantly sooner using the front-weighted track start (0.80 s) than the other two starts (both 0.87 s; P< 0.001). In the rear-weighted track start, however, the athletes left the blocks with significantly higher horizontal velocity than in the grab or front-weighted track start (3.99 vs. 3.87 and 3.90m/s, respectively; each P < 0.001). By 5 m, the front-weighted track start maintained its time advantage over the grab start (2.19 vs. 2.24s; P= 0.008) but not the rear-weighted track start (2.19 vs. 2.21s; P= 0.336). However, the rear-weighted track start had a significant advantage over the front-weigh ted track start in terms of instantaneous horizontal velocity at 5 m (2.25 vs. 2.18m/s; P = 0.009). Therefore, the rear-weighted track start had a better combination of time and velocity than the front-weighted track start. There was also a trend for the rear-weighted track start to have higher velocity at 5m than the grab start, although this did not reach statistical significance (2.25 vs. 2.20m/s; P = 0.042). Overall, these results favour the rear-weighted track start for female swimmers even though most of the athletes had little or no prior experience with it. Additional research is needed to determine whether males would respond similarly to females in these three different swimming starts.